Effect of Adenosine Receptor Antagonists on Adenosine-Pretreated PC12 Cells Exposed to Paraquat - Liangcheng Shang; Yaobiao Huang; Xin Xie; Sudan Ye; Chun Chen (SAGE Publishing, 2022)
Previous studies evaluated the adenosine receptor antagonists alone to determine their effects on oxidative stress, but little is known about adenosine's protective efficacy when oxidative injury occurs in vivo. Adenosine is a crucial signaling molecule recognized by four distinct G-protein-coupled receptors (GPCRs) (i.e., A1R, A2AR, A2BR, and A3R) and protects cells against pathological conditions. The present study was performed to evaluate the role of antagonist modulation in the setting of paraquat toxicity with adenosine pretreatment. First, PC12 cells were exposed to paraquat (850 μM) and adenosine (30 μM) to develop an in vitro model for the antagonist effect assay. Second, we found that the A1R antagonist DPCPX enhanced the viability of paraquat-induced PC12 cells that underwent adenosine pretreatment. Moreover, the A2AR antagonist ZM241385 decreased the viability of paraquat-induced PC12 cells that underwent adenosine pretreatment. Our findings indicate that adenosine protection requires a dual blockade of A1R and activation of A2AR to work at its full potential, and the A2B and A3 adenosine receptor antagonists increased paraquat-induced oxidative damage. This represents a novel pharmacological strategy based on A1/A2A interactions and can assist in clarifying the role played by AR antagonists in the treatment of neurodegenerative diseases.